What Drives Students to Continue Further Study in Unsupporting Environments? (Case Study on Alumni of SMK Muhammadiyah 1 Sragen) - Ramadhanni, Noor Wahyu; Mustofa, Rochman Hadi (Proceedings International Conference on Education Innovation and Social Science, 2022)
This study aimed to analyze the motivation, factors, and constraints of SMK Muhammadiyah 1 Sragen graduates in continuing their education. The research method used is descriptive qualitative research with a case study design—data collection techniques using direct or indirect interviews. The results showed that the graduates of SMK Muhammadiyah 1 Sragen who continued their education to higher education were formed based on their own volition, the socioeconomic status of their parents, family environment, school environment, and community environment. The obstacles experienced in choosing to continue their education to higher education are the economic constraints of parents, but this can be overcome by finding universities with affordable tuition fees and finding solutions by registering for lectures through scholarships.